SIMULASI KEBIJAKAN PENINGKATAN PRODUKSI DAN PENDAPATAN USAHATANI PADI System of Rice Intensification (SRI) - Non SRI (Studi Kasus di Kecamatan Sukorejo Kabupaten Pasuruan) - Wenny Mamilianti (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2010)
Serious efforts should be given to padi production enhancement continuously though government has executed various programs over time. These programs included SRI system technology innovation and policy reinforcement that could enhance padi productivity. This research focused to evaluate various policy alternatives by designing the model and executing policy simulation beforehand. The objectives of this research were to analyze the SRI-Non SRI padi production performance and farming revenue model and to analyze policy simulation implication that could enhance padi farming production and revenue. The research results showed that the accomplished model was feasible to execute analysis and forecasting. At seed utilization equation, the dummy coefficient signed negative and gave significant effect, it meant that SRI system used fewer seeds. The price of unorganic fertilizer gave significant effect to unorganic fertilizer and MOL utilization. The amount of livestock belonged to farmer affected compost utilization. At the equation of production, unorganic fertilizer gave no effect, the seeds had negative sign and gave significant effect, while MOL, compost, nonfamilial labour gave significant effect and SRI system production was greater than Non SRI showed by positive signed dummy coefficient. Policy simulation (1) the implications of unorganic fertilizer price increase of 30% were profit decreased production cost increased, production increased, unorganic fertilizer utilization decreased, MOL increased; (2) the implications of industry labor wage increase policy were profit decreased, production cost remained unchanged, production decreased, and nonfamilial labor employment decreased; (3) the effects of compost from livestock policy were profit increased, production cost increased, production increased, and compost utilization increased as well. This research encouraged farmers to own livestock to guarantee the availability of compost, gave serious efforts to farmers in order they would apply SRI system which proved could increase padi farming production and revenue and enhance farmers prosperity all at once.Keywords : Policy, Production, Revenue, System of Rice Intensification (SRI)